Otoliths of five extant species of the annual killifish Nothobranchius from the East African savannah. - Bettina Reichenbacher; Martin Reichard (PLoS ONE, 2014)
This study presents, for the first time, a comprehensive dataset that documents the range of inter- and intraspecific otolith variation in aplocheiloid killifish, based on a total of 86 individuals representing five extant species of Nothobranchius PETERS, 1868, from East Africa: the sympatric pairs N. rubripinnis SEEGERS, 1986 and N. ruudwildekampi COSTA, 2009 (Eastern Tanzania), and N. orthonotus (PETERS, 1844) and N. furzeri JUBB, 1971 (Southern Mozambique), and two isolated populations of N. korthausae MEINKEN, 1973 (Eastern Tanzania). Otolith characters were analysed based on SEM images, and otolith morphometry was conducted using uni- and multivariate statistics. Two ancient clades of probably Early to Middle Miocene age in eastern Tanzania and southern Mozambique can be recognized based on otolith morphologies, which is consistent with previous work based on molecular data. The distinctive sulcus morphologies in the otoliths of sympatric species may be linked to species-specific hearing capabilities, perhaps constituting a case of character displacement in an area of secondary sympatry. The otoliths of the studied species of Nothobranchius are diagnostic at the species level, even in the case of closely related species diagnosable otherwise only by minor differences in coloration. The two populations of N. korthausae also displayed some differences in their otolith characters. The new data may facilitate future recognition of fossil species of Nothobranchius. As no fossil remains of extant aplocheiloid killifishes have yet been described, the discovery of fossil otoliths of Nothobranchius would significantly advance understanding of the evolutionary history of this interesting group of fishes.